To see and be seen. An interpretation of the reward scenes in the Amarnian funerary narrative: the ‘enabling’ audience - Yomaha, Silvana (Instituto de Arqueología, Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2020)
In the Amarnian era, the ritual of the public appearance of the pharaoh through the palace window, accompanied by the royal family, can be interpreted as a monarchical control device but also as a performative component of social practices. The instructive experience is fundamental because it is within this public act –depicted on the walls of the court officer private tombs– that the political, social, economic, and fundamentally symbolic relationships that characterize the Akhenaten’s reign, are shown. The main goal of this paper is to analyze the delivery of livelihoods and luxury items from the hands of the pharaoh to his most faithful servants as a ritual. It is intended to demonstrate the effectiveness of the material and symbolic power of the monarchy sustained by the bureaucracy and by the Aton divinity. All of this is manifested in the representation of the scene of giving rewards to priests, generals, and administrators from the window of appearance in the presence of an audience set up by key spectators (foreign ambassadors, bureaucrats, priests, soldiers, the community in general) to complete the effectiveness of the act.